2010
DOI: 10.1590/s0102-311x2010000600016
|View full text |Cite
|
Sign up to set email alerts
|

Os custos de doenças tabaco-relacionadas para o Sistema Único de Saúde

Abstract: This study aimed to identify the direct costs of hospitalizations due to three smoking-related groups of diseases -cancer and circulatory and respiratory diseases -in Brazil's Unified National Health System (SUS) 2 . O tabagismo gera uma carga econômica substantiva para as sociedades, caracterizada pelos custos da assistência médica e da perda de produtividade devido à morbidade e à morte prematura 3 .Nos últimos anos, observa-se um crescimento da aplicação do instrumental da análise econômica em saúde par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
0
18
0
17
Order By: Relevance
“…Results from a national survey indicate that in 2008 prevalence was 18.5%, showing a significant reduction when compared with the 1989 data 10 . Advances in tobacco control in Brazil seen over the last decades are positive, but it is observed that prevalence among young women is growing more than among men of the same age 11 , mortality is still high 12,13 and the costs are underestimated 14 . In this scenario, calculation of the tobacco-related disease burden is not often made in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a national survey indicate that in 2008 prevalence was 18.5%, showing a significant reduction when compared with the 1989 data 10 . Advances in tobacco control in Brazil seen over the last decades are positive, but it is observed that prevalence among young women is growing more than among men of the same age 11 , mortality is still high 12,13 and the costs are underestimated 14 . In this scenario, calculation of the tobacco-related disease burden is not often made in the country.…”
Section: Introductionmentioning
confidence: 99%
“…11 Hence, it are the amounts spent on the execution of the purchase of materials or the hiring of workforce. 12 The indirect cost, on the other hand, requires an assessment process, as individual measuring is impossible, since it includes: physical structure, electrical energy, water, electricity, depreciation.…”
Section: Methodsmentioning
confidence: 99%
“…One involves the cost of tobacco-related diseases for the country's Brazilian Unified National Health System (SUS). According to a recent study 24 , in 2005 some 35% of hospitalizations in men and 27% in women in the SUS were attributed to smoking, involving diseases of the respiratory and circulatory systems and cancer. The decision made by "funneling" 12 must have been made to relieve this financial burden.…”
Section: Final Remarksmentioning
confidence: 99%